Dioscorea bulbifera induced apoptosis through inhibition of ERK 1/2 and activation of JNK signaling pathways in HCT116 human colorectal carcinoma cells - Hidayat, Ahmad Fadhlurrahman Ahmad; Chan, Chim Kei; Mohamad, Jamaludin; Abdul Kadir, Habsah (Elsevier, 2018)
Dioscorea bulbifera, also known as air potato, has been cultivated as food crop mainly in tropical countries in Asia and Australia. The tubers are edible and have often been used in Traditional Chinese Medicine (TCM) and Ayurvedic medicine to treat cancer, diabetes, thyroid disease, and inflammation. This study aimed to investigate the effects of D. bulbifera on HCT116 human colorectal carcinoma cells and to unravel the plausible mechanisms underlying its apoptotic effects. The ethanol crude and fractions (hexane, ethyl acetate and water) of D. bulbifera were subjected to cell viability MTT assay against various cancer cell lines. The lowest IC50 of the extract and fractions on selected cancer cells were selected for further apoptosis assay and western blot analysis. HCT116 cancer cells were treated with D. bulbifera and stained with Annexin/PI or Hoechst 33342/PI for preliminary confirmation of apoptosis. The dissipation of mitochondria membrane potential (MMP) was determined by flow cytometry. The protein expressions of apoptosis-related proteins such as Bcl-2 family, caspases, Fas, PARP, ERK1/2 and JNK were detected by western blot analysis. Moreover, the HCT116 cells were treated with UO126 and SP600125 inhibitors to verify the involvement of ERK1/2 and JNK protein expressions in inducing apoptotic cell death. Based on the result, D. bulbifera ethyl acetate fraction (DBEAF) exhibited the most compelling cytotoxicity on HCT116 cells with an IC50 of 37.91 ± 1.30 µg/mL. The induction of apoptosis was confirmed by phosphatidylserine externalization and chromatin condensation. Depolarization of MMP further conferred the induction of apoptosis was through the regulation of Bcl-2 family proteins. Activation of caspase cascades (caspase-3, -9, -8 and -10) was elicited followed by the observation of cleaved PARP accumulation in DBEAF-treated cells. Furthermore, death receptor, Fas was activated upon exposure to DBEAF. Collective apoptotic evidences suggested the involvement of intrinsic and extrinsic pathways by DBEAF in HCT116 cells. Interestingly, the attenuation of ERK1/2 phosphorylation accompanied by the activation of JNK was detected in DBEAF-treated cells. In conclusion, the findings revealed that DBEAF induced apoptosis through intrinsic and extrinsic pathways involving ERK1/2 and JNK.